Promoting environmental literacy for prospective teacher: How does Scopus AI illustrate valuable lessons from Indonesia? - H. Husamah; Jalilah Azizah; Tutut Indria Permana; Yanur Setyaningrum; Iin Hindun; Roimil Latifa (Universitas Muhammadiyah Malang, 2025)
Environmental literacy is increasingly critical for prospective teachers, yet teacher-education initiatives remain fragmented. Using Scopus AI as an analytic lens, this study synthesizes Scopus-indexed evidence to identify how Indonesia promotes environmental literacy in pre-service teacher preparation. We conducted a natural-language search and a complementary keyword strategy covering environmental/eco literacy, sustainability education, teacher education, curriculum, pedagogy, and outcomes, and analyzed the retrieved summaries and visual outputs through qualitative thematic synthesis and critical policy analysis. Results highlight recurring strategies: integrating critical thinking and ecoliteracy, using validated instruments (e.g., spirituality-based environmental literacy measures), strengthening school programs such as Adiwiyata, applying EESD-oriented materials, and implementing guided inquiry, project-based/STEAM approaches, and STEM integrated with local wisdom. The derived concept map shows four reinforcing pathways—community engagement, curriculum integration, teacher development, and HEI-led educational strategies—linked by critical reflection toward responsible behavior. These insights support more coherent program design and scalable policy alignment in teacher education across contexts.